Awareness of risk and safety preparedness among hikers in Bukit Tabur - Khairi, Nurfarhana; Ahmad Zawawi, Azita (Forestry Department Peninsular Malaysia, 2022)
Repeated incidents and hikers' awareness of risk had become a prolonged issue in Bukit Tabur, an adventurous hiking spot. Understanding of risk and safety is vital to be nurtured among hikers. This study was conducted to examine the hikers' awareness and knowledge of potential risks during hiking, hikers' attention to safety preparedness, and the relationship between experience and safety preparedness towards hiking activity. Data was collected from 468 respondents among those who had hiking experience in Bukit Tabur. The result suggested that hikers are aware of potential risks during hiking. However, the awareness of risk caused by human factors is more significant than awareness of environmental factors. Surprisingly, only 50% to 60% of hikers showed explicit knowledge and precise information about the study area. Hikers' awareness of safety preparedness is high, where the findings highlight that a healthy body and fitness are crucial elements. Interestingly, the study suggested that in the case of Bukit Tabur, experience has a low influence on safety preparedness for the hiking activity.